White paper on microbial anti-cancer therapy and prevention. Issue 1 (6th August 2018) - Forbes, Neil S.; Coffin, Robert S.; Deng, Liang; Evgin, Laura; Fiering, Steve; Giacalone, Matthew; Gravekamp, Claudia; Gulley, James L.; Gunn, Hal; Hoffman, Robert M.; Kaur, Balveen; Liu, Ke; et al.
Abstract : In this White Paper, we discuss the current state of microbial cancer therapy. This paper resulted from a meeting ('Microbial Based Cancer Therapy') at the US National Cancer Institute in the summer of 2017. Here, we define 'Microbial Therapy' to include both oncolytic viral therapy and bacterial anticancer therapy. Both of these fields exploit tumor-specific infectious microbes to treat cancer, have similar mechanisms of action, and are facing similar challenges to commercialization. We designed this paper to nucleate this growing field of microbial therapeutics and increase interactions between researchers in it and related fields. The authors of this paper include many primary researchers in this field. In this paper, we discuss the potential, status and opportunities for microbial therapy as well as strategies attempted to date and important questions that need to be addressed. The main areas that we think will have the greatest impact are immune stimulation, control of efficacy, control of delivery, and safety. There is much excitement about the potential of this field to treat currently intractable cancer. Much of the potential exists because these therapies utilize unique mechanisms of action, difficult to achieve with other biological or small molecule drugs. By better understanding and controlling these mechanisms, we will create new therapies that will become integral components of cancer care.